Maladaptive innate immune training of myelopoiesis links inflammatory comorbidities - Li, Xiaofei; Wang, Hui; Yu, Xiang; Saha, Gundappa; Kalafati, Lydia; Ioannidis, Charalampos; Mitroulis, Ioannis; Netea, Mihai G.; Chavakis, Triantafyllos; Hajishengallis, George (Cell, 2022)
Bone marrow (BM)-mediated trained innate immunity (TII) is a state of heightened immune responsiveness of hematopoietic stem and progenitor cells (HSPC) and their myeloid progeny. We show here that maladaptive BM-mediated TII underlies inflammatory comorbidities, as exemplified by the periodontitis-arthritis axis. Experimental-periodontitis-related systemic inflammation in mice induced epigenetic rewiring of HSPC and led to sustained enhancement of production of myeloid cells with increased inflammatory preparedness. The periodontitis-induced trained phenotype was transmissible by BM transplantation to naive recipients, which exhibited increased inflammatory responsiveness and disease severity when subjected to inflammatory arthritis. IL-1 signaling in HSPC was essential for their maladaptive training by periodontitis. Therefore, maladaptive innate immune training of myelopoiesis underlies inflammatory comorbidities and may be pharmacologically targeted to treat them via a holistic approach. [Display omitted] •Experimental periodontitis (EP) induces maladaptive trained myelopoiesis•EP-induced trained phenotype is transmissible by bone marrow transplantation•IL-1 signaling in hematopoietic progenitors mediates maladaptive training by EP•Maladaptively trained myelopoiesis links the periodontitis-arthritis comorbidity Trained innate immune responses contribute to pathology of a comorbid condition, as seen with arthritis after periodontitis in animal models.